Sustainable construction techniques : From structural design to material selection: Assessing and improving the environmental impact of buildings - El khouli, Sebastian; John, Viola; Zeumer, Martin (DETAIL Green Books., 2015)
The book offers a thorough guide to ecological building design and sustainable construction methods. The authors provide an overview of the most relevant databases and certification standards for building products and illustrate how a Life Cycle Analysis is conducted. They identify key ways of optimising the planning process in line with ecological criteria, while offering advice for the selection of building materials and elements.